Analisis Pengaruh Liquiditas, Leverage dan Sales Growth terhadap Kinerja Perusahaan pada Sektor Teknologi yang Terdaftar di Bei - Sovika Dian Arekha Mayang; Dianing Widya Kusumaastuti (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study focuses on accelerating digital transformation post-COVID-19 pandemic, which requires technology companies to maintain financial stability and performance. The objective of this study is to examine the impact of liquidity, leverage, and sales growth on the performance of technology companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Using a quantitative approach, this study involved 27 companies (135 observations) selected using purposive sampling, with ROA as the dependent variable, while Current Ratio, Debt-to-Equity Ratio, and sales growth as independent variables. The results of multiple linear regression analysis indicate that liquidity and leverage have no significant effect on ROA, while sales growth has a significant positive effect. Simultaneously, these three variables have a significant effect, contributing 31%, indicating that sales growth is the dominant factor driving technology company performance in the digital era, while liquidity and leverage do not show a direct impact. These findings provide important implications for management, investors, and regulators in formulating adaptive financial strategies.